المناخ واثره على كفاءة العمل وراحة الانسان بمدينة نالوت - د. حسين محمد عبدالله الجديع (Aljameai, 2022)
الملخص:يعد المناخ أحد أهم المتغيرات البيئية التي تؤثر على جميع أنشطة الانسان وراحته، وتعتبر العلاقة بين المناخ والانسان ذات أهمية كبيرة في الدراسات المناخية، وتركز أبعاد الدراسة في موضوع هذه الورقة البحثية على دراسة أثر المناخ على نشاط العمل ،وراحة الانسان من وجهة نظر المناخ التطبيقي ،حيث تم تطبيق العديد من المعايير والقرائن مثل (قرينة ثوم أو قرينة الحرارة الفعالة ،مؤشر تبريد الرياح)، لتحيد أفضل الأوقات المناسبة للعمل والأوقات التي يشعر فيها الانسان بالراحة أو الانزعاج ، وأظهرت النتائج أن الفترة المثالية للراحة بمدينة نالوت تكون خلال شهري أكتوبر ومايو ، بينما أشهر الصيف وأول أشهر الخريف غير مناسبة للعمل ولا للإنتاج، وأوصت الدراسة بتجنب الأعمال الشاقة خلال الفصل الحار من السنة، والتوسع في زراعة الأشجار والمساحات الخضراء.Abstract:Climate is one of the most important environmental variables that affect all human activities and comfort. The relationship between climate and human being is of great importance in climatic studies. The dimensions of the study in the subject of this research paper are based on studying the impact of climate on work and, human comfort from the applied climate perspective.  Several criteria and indicators have been applied such as (Thom’s formula, temperature humidity index, wind chill  index,) to determine the best suitable times for work and the times when people feel comfortable/uncomfortable. On the one hand, the results of the study showed that the ideal period for relaxation in the city of Nalut is during the months of October and May. While on the other hand, the summer months and the first months of autumn are not suitable for both of work and production. The study recommends avoiding hard work during the hot season of the year, expanding the planting of trees and green spaces.